Outcomes of importance to children and young adults with cerebral palsy, their parents and health professionals following lower limb orthopaedic surgery: A qualitative study to inform a Core Outcome Set. (27th January 2022) - Almoajil, Hajar; Toye, Francine; Dawes, Helen; Pierce, Jo; Meaney, Andrew; Baklouti, Aziz; Poverini, Lara; Hopewell, Sally; Theologis, Tim
Abstract: Introduction: Although several outcomes are commonly measured to assess the effect of surgery for young people with cerebral palsy (CP), these are selected mainly by health professionals and researchers. Including the perspectives of a broader range of stakeholders is an essential step towards determining important outcomes for assessment. This qualitative study involves the development of a core outcome set (COS) for lower limb orthopaedic surgery for ambulant children with CP. Objective: This study aimed to identify outcomes that matter to children and young people with CP, their parents and healthcare professionals following lower limb orthopaedic surgery. Methods: Semi‐structured interviews were conducted with 10 healthcare professionals, 10 children and young people with CP and 8 parents. Interview data were analysed by content analysis supported by the International Classification of Functioning, Disability and Health (ICF‐CY) supplemented by thematic analysis. Findings: Thirty‐one outcomes were identified in total, which were linked to eleven second‐level ICF‐CY categories. There were differences between stakeholder groups in preferences and expectations from surgical outcomes. Healthcare professionals and children with their parents identified 31 and 25 outcomes, respectively. Health outcomes valued by participants were lower limb alignment and symmetry, flexibility and muscle strength, mental health, fatigue, pain, function in life, mobility, participation, being independent, quality of life and adverse events. Compared to previous published trials, 10 new outcomes were revealed by this study. Conclusion: The researchers identified outcomes that are important to all stakeholders following lower limb orthopaedic surgery for ambulant CP. Including these outcomes in future studies would promote patient‐centred care for children and young adults with CP. Findings will be used to inform an international Delphi survey and develop a COS in this field. Patient and Public Contribution: This study was informed by an advisory group including a young adult with CP and a parent of a child with CP. This group engaged in the design of the study and the information material to support the interview (information sheet and interview topic guide).